Protein-polysaccharide complexes and conjugates: Structural modifications and interactions under diverse treatments - Ashley Babu; Rafeeya Shams; Kshirod Kumar Dash; Ayaz Mukarram Shaikh; Béla Kovács (Journal of Agriculture and Food Research)
Proteins and polysaccharides are two essential biopolymers, each with unique functional properties. Proteins are known for their foaming, emulsifying, and gelling abilities but often face stability and solubility challenges, making them sensitive to environmental factors like light, temperature, and pH. In contrast, polysaccharides are known for their solubility and strong mechanical properties. When combined, these biopolymers demonstrate enhanced functional characteristics, a phenomenon known as synergy, which opens up various opportunities in the nutraceutical, pharmaceutical, and food industries. This review explores the interactions between proteins and polysaccharides through both covalent and non-covalent bonds. It examines how these biopolymers respond to external conditions such as temperature, pH, humidity, pressure, and salt concentration. Additionally, it briefly addresses how variations in concentration, ratios, and types within the biopolymers influence protein-polysaccharide interactions. Moreover, protein-polysaccharide complexes are extensively utilized in various applications that involve both sophisticated and conventional treatments including gamma irradiation, high-pressure processing, microwave heating, UV radiation, electron beam irradiation, pulsed electric fields, fermentation, and ultrasonication. Therefore, studying their behaviour and changes in interactions under different treatments is crucial. This review offers a brief overview of how these interactions are affected by various treatment processes.